2003
DOI: 10.1099/jmm.0.05079-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute viral gastroenteritis: proportion and clinical relevance of multiple infections in Spanish children

Abstract: Dual infections associated with acute infectious diarrhoea and its microbiological, epidemiological and clinical findings have been evaluated in patients selected from a comprehensive survey of children under 4 years old, admitted to hospital emergency rooms from October 1996 to November 1997. A total of 820 children (433 males and 387 females) were enrolled. Stools were tested for rotavirus, adenovirus, astrovirus and bacterial enteropathogens. Patients were grouped according to age, and the seasonality of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
52
4
22

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 17 publications
16
52
4
22
Order By: Relevance
“…Co-infection of astrovirus with other viruses has also been observed in studies carried out by Román et al (2003) and Phan et al (2004) in Spain and Pakistan, respectively. In this study, although the association of astrovirus with AG has been demonstrated, a larger proportion (30.4%) of samples was also positive for other viruses making it difficult to determine the primary viral pathogen.…”
Section: Discussionmentioning
confidence: 83%
“…Co-infection of astrovirus with other viruses has also been observed in studies carried out by Román et al (2003) and Phan et al (2004) in Spain and Pakistan, respectively. In this study, although the association of astrovirus with AG has been demonstrated, a larger proportion (30.4%) of samples was also positive for other viruses making it difficult to determine the primary viral pathogen.…”
Section: Discussionmentioning
confidence: 83%
“…This study found that the highest proportion of dual infections was identified in February, March and April months and seasonal occurrence of some mono-infections such as Rotavirus is more frequent in winter and spring. At the same study that performed in Spain, most of the cases with mixed infection occurred in autumn (26 cases in autumn, 5 in winter, 6 in spring, 2 in summer), and no seasonal differences were detected between the different co-infections 19 . As seen in the present study, Rotavirus is the most common isolated viral agent (40.74%) for acute childhood diarrhea.…”
Section: Discussionmentioning
confidence: 98%
“…Most of the studies have mentioned that mixed infections were less frequent than mono-infections. A study that performed in Spain showed that the most frequent mixed infections were Rotavirus-Astrovirus (13 cases) and RotavirusAdenovirus (10 cases in 820 stool samples) infections 19 . This study found that the highest proportion of dual infections was identified in February, March and April months and seasonal occurrence of some mono-infections such as Rotavirus is more frequent in winter and spring.…”
Section: Discussionmentioning
confidence: 99%
“…(17) 'nın yaptıkları çalış-mada farklı viruslerin birlikteliği % 0.6-9.6 arasında bildirilmiş olup en sıklıkla rotavirus ve adenovirus birlikteliği gözlenmiştir. İspanya'da yapılan bir çalışmada ise rotavirus-astrovirus koenfeksiyonu daha çok bildirilmiş (% 1.6), rotavirus-adenovirus koenfeksiyonu ise vakaların % 1.2'sinde saptanmıştır (19) . Rotavirus enfeksiyonun mevsimsel dağılımı coğrafi farklılıklar göstermekle birlikte genellikle kış aylarında artış göster-mektedir (1,8,13,26) .…”
Section: Bulgularunclassified
“…Çalışmamızda adenovirus vakaları en fazla kış mevsiminde görülmüştür. Norovirus vakalarının dağılımı ile ilgili olarak yaz veya kış aylarında artış bildirilmiştir (5,19,21) . Ancak Bozkurt ve ark.…”
Section: Bulgularunclassified